Desain Media Pembelajaran Prakarya Berbasis Smart Apps Creator - Nasir Nasir; Nurindah Nurindah; Alfira Rauf; Sadriana Ayu; Uyunnasirah Hambali (Universitas Cokroaminoto Palopo, 2022)
The aims of this study is to produce learning media in Android-based craft subjects through valid and practical smart apps creator applications at SMPN 12 Bulukumba. The research method used is the Research and Development (R&D) method. The development model used refers to the 4D development model (Four D-Model) consisting of 4 stages, namely: define, design, development and dessimeninate. However, this research was only carried out at the development stage. Because this research is only limited to developing and producing Android-based learning media products through smart application maker applications. The research was conducted in class VII SMPN 12 Bulukumba with 30 students and 1 teacher. The research instruments used were media and material expert validation sheets, student and teacher response questionnaires. The data collection technique used was the validation test and student response questionnaires. The results of the development show that learning media based on smart apps creator based on the assessment aspect obtained an average value of 3.70 with a very valid category. Meanwhile, the assessment of material experts is also in a very valid category with an average value of 3.70. The results of the small group trial assessment obtained an average value of 3.27 in the good category. While the results of the small group test obtained an average of with practical criteria while in the limited field test an average score of = 3.44 with very practical features and for teacher responses obtained an average average =3.65 with very practical features. Based on the results of research conducted through the development process, the researchers concluded that the learning media developed were valid and practical to use